Strategic planning for regeneration of inefficient urban fabric - Arefeh Mahmoodi (مهندسی و مدیریت ساخت)
Strategic planning of urban development is a new approach in urban planning and management, which relies on the principles of sustainable urban development, drawing a vision, formulating development goals, comprehensive and systematic confrontation with the basic problems of the city, and one of the strategies to achieve urban development is the sustainable regeneration of the fabric. Planning in worn-out urban areas has always been the most important issue of urban planning, and one of the strategies to achieve urban development is the sustainable regeneration of worn-out urban tissues. Strategic planning is used in order to properly deal with the future and solve the current complex problems. Urban development strategy focusing on strengthening economic competitiveness and reducing poverty and various environmental aspects of the city, urban spatial structure, infrastructure structures, cultural and social aspects, etc. It is the best option to achieve sustainable urban development. So far, the plans and programs that have been implemented to intervene in inefficient structures. Most of them have physical goals and they have ignored the main assets of these tissues in which the people live. Therefore, in order to solve the problems of the inefficient texture of the cities in the economic, social, cultural and physical fields, it is necessary to use effective approaches in this field, in order to take effective steps in order to preserve their identity and promote them, and by using a planning In a coherent manner and with the participation of all interested groups, he paid for the comprehensive improvement of these inefficient tissues.